Adaptation of Urban High-density Neighbourhoods in Nodes of Sustainable Intelligent Mobility Condensers - Prados Gómez, Carlos; Rosa-Jiménez, Carlos; Márquez-Ballesteros, María José; García-Moreno, Alberto Enrique (My University, 2021)
In Europe and since the early twentieth century, municipal mobility policies have provided underground parking and public transport to many of the rapidly built social neighbourhoods between 1960 and 1980, which were planned lacking them. However, the climatic emergency requires new approaches that reduce CO2 emissions. This paper sets out the steps for the implementation of an Intelligent Mobility Condenser (IMC) in an existing neighbourhood. IMCs combine connectivity to public transport, together with the creation of a transport cooperative that meets the mobility needs of its neighbours without the need to own a private car. Similar to car-sharing, the IMC offers hybrid, electric, solar cars, along with motorcycles and electric bicycles. This together with a digital platform that facilitates the management of their needs. On the other hand, IMCs are automatic surface parkings, with solar collection and urban gardens, which, being high-access nodes in the neighbourhood, allow the incorporation of community, social and commercial spaces. The paper discusses the results based on the economic and environmental benefits of the model, and the threats of its implementation due to the difficulties of giving up the private car.
Keywords: Tráfico urbano - Aspectos ambientales; Automóviles - Aspectos ambientales; Ciudades - Contaminación - Control; Neighbourhood mobility; Car-sharing; Smart mobility; Transport cooperative